This will all be over soon eaudiobook A memoir. - Strong, Cecily (Memoir of Loss and Love., 2021)
A powerful memoir from the Saturday Night Live cast member Cecily Strong about grieving the death of her cousin—and embracing the life-affirming lessons he taught her—amid the coronavirus pandemic. Cecily Strong had a special bond with her cousin Owen. And so she was devastated when, in early 2020, he passed away at age thirty from the brain cancer glioblastoma. Before Strong could attempt to process her grief, another tragedy struck: the coronavirus pandemic. Following a few harrowing weeks in the virus epicenter of New York City, Strong relocated to an isolated house in the woods upstate. Here, trying to make sense of Owen's death and the upended world, she spent much of the ensuing months writing. The result is This Will All Be Over Soon —a raw, unflinching memoir about loss, love, laughter, and hope. Befitting the time-warped year of 2020, the diary-like approach deftly weaves together the present and the past. Strong chronicles the challenges of beginning a relationship during the pandemic and the fear when her new boyfriend contracts COVID. She describes the pain of losing her friend and longtime Saturday Night Live staff member Hal Willner to the virus. She reflects on formative events from her life, including how her high school expulsion led to her pursuing a career in theater and, years later, landing at SNL . Yet the heart of the book is Owen. Strong offers a poignant account of her cousin's life, both before and after his diagnosis. Inspired by his unshakable positivity and the valuable lessons he taught her, she has written a book that—as indicated by its title—serves as a moving reminder: whatever challenges life might throw one's way, they will be over soon. And so will life. So make sure to appreciate every day and don't take a second of it for granted.